2008
DOI: 10.2478/s11687-008-0037-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in parasite occurrence and microhabitat distribution of monogenean parasites of gudgeon Gobio gobio (L.)

Abstract: SummarySeasonal changes in occurrence, infracommunity composition and microhabitat distribution of the monogenean parasites of gudgeon Gobio gobio (L.) were studied during two years in the River Haná (Czech Republic). Altogether 212 specimens of gudgeon were examined and a total of 6456 specimens of eight monogenean species were recorded: Dactylogyrus cryptomeres, Gyrodactylus gobiensis, Gyrodactylus gobii, Gyrodactylus gasterostei, Gyrodactylus vimbi, Gyrodactylus markakulensis, Gyrodactylus sedelnikowi and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…For example, Drovskikh and Torba (1988) reported that Dactylogyrus intermedius and D. wegeneri on Carrasius carrasius changed their positions on the gills in conditions of prolonged oxygen deprivation. In the case of the thermophilous species Gyrodactylus markakulensis, it is reported that 94 % of parasites occurred on the fins in warm months but preferred the gill apparatus during cold months when conditions for survival were not favourable (Blazek et al 2008). Similarly, Koskivaara et al (1991) found gyrodactylids to be more frequently attached on the gills when environmental conditions were not suitable for parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Drovskikh and Torba (1988) reported that Dactylogyrus intermedius and D. wegeneri on Carrasius carrasius changed their positions on the gills in conditions of prolonged oxygen deprivation. In the case of the thermophilous species Gyrodactylus markakulensis, it is reported that 94 % of parasites occurred on the fins in warm months but preferred the gill apparatus during cold months when conditions for survival were not favourable (Blazek et al 2008). Similarly, Koskivaara et al (1991) found gyrodactylids to be more frequently attached on the gills when environmental conditions were not suitable for parasites.…”
Section: Discussionmentioning
confidence: 99%
“…(Llewellyn 1956;Rhode 1977aRhode , b, 1979Lebedev 1978). A great deal of work has been carried out on microecology (Niche restriction) of ectoparasites of fishes covering marine and freshwater fishes from different geographic regions (Rhode 1977a(Rhode , b, 1979(Rhode , 1980(Rhode , 1981(Rhode , 1982(Rhode , 1989(Rhode , 1994Rhode and Watson 1985;Rhode and Hobbs 1986;Geets et al 1997;Hanek and Fernando 1978;Koskivaara et al 1992;Lambert and Maillard 1975;Ramasamy and Ramalingam 1989;Ramasamy et al 1985;Dzika 1999;Morand 2000, 2001;Yang et al 2006;Blazek et al 2008;Soyulu et al 2010;Tripathi et al 2010). Various hypotheses such as intra and interspecific competition, ventilating water currents and optimisation of reproductive strategy have been put forward to explain the microhabitat restriction and niche specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial parasite distribution is supposed to result from water flow over the gills in the course of respiration [41]. Most of the respiratory water flows via the III pair of gill arches and the lesser amounts flow through the II and IV gill pairs [49]. Variations in surface area or water flow among the various components of the gill arches have a critical influences in defining the distribution of the parasite on the gills [50].…”
Section: Community Components Of Dactylogyrid Speciesmentioning
confidence: 99%
“…Infection by Dactylogyrus causes lesions in the gill epithelium during attachment and these lesions are caused by the 14 marginal hooks and 2 anchors of the attachment organ. As they possess a direct life cycle, they can reach epizootic levels very quickly when hosts and parasites are confined close together (Thoney and Hargis 1991;Blazek et al 2008).…”
Section: Introductionmentioning
confidence: 99%